The role of health insurance in the coverage of oral health care in Senegal - Mbathio Diop; Aida Kanouté; Massamba Diouf; Amadou Diaw Ndiaye; Cheikh Mouhamadou Mbacké Lo; Daouda Faye; Daouda Cissé (AOSIS, 2018)
Oral diseases costs are among the most expensive health care benefits. In Senegal, households contribute up to 37.6% of the national health spending through direct payments. The aim of this work was to study the role of health insurance in the coverage of oral health care in Senegal. The study was based on health insurance agents and policyholders. The study reveals that oral health care coverage through health insurance still does not meet requirements for treatment of oral infections. In financial terms, oral health care costs health insurance too much. As a result, carriers cover them partially. On top of that, the majority of the population's lack of knowledge about mutual, because they have a little background on oral health care, the latter weighs heavily on health insurance leading to the use of self-medication, traditional medicine and handicraft prosthetists. The analysis reveals an unequal access to oral health care through the health insurance system. To bring under control the expenditure for oral health care, carriers and dental surgeons must work together to raise the populations' awareness on community solidarity.